2008
DOI: 10.1016/j.visres.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between complex motion patterns in the perception of shape

Abstract: We investigated how different types of complex motion patterns interact in the perception of shape. We used global dot-motion stimuli which consisted of two superimposed groups of dots; one group of dots moved along an ellipsoidal trajectory (target pattern), while the other group of dots was divided into quadrants with dots in alternating sectors moving in radial expanding and radial contracting directions (background pattern). In the first experiment, observers judged whether the major axis of an ellipsoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In three experiments, the relative contribution of motion streaks to the perception of motion was examined by changing dot speed, dot contrast, and dot lifetime to generate shortened streaks. Previous investigations have shown that such manipulations impact on the availability of motion streaks in the computation of motion direction (Apthorp & Alais, 2009;Apthorp et al 2010;Edwards & Crane, 2007;Li et al, 2008). Experiment 1 examined the effect of dot speed on the extent of tilt induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three experiments, the relative contribution of motion streaks to the perception of motion was examined by changing dot speed, dot contrast, and dot lifetime to generate shortened streaks. Previous investigations have shown that such manipulations impact on the availability of motion streaks in the computation of motion direction (Apthorp & Alais, 2009;Apthorp et al 2010;Edwards & Crane, 2007;Li et al, 2008). Experiment 1 examined the effect of dot speed on the extent of tilt induction.…”
Section: Discussionmentioning
confidence: 99%
“…If motion-tilt induction does indeed arise from lateral inhibition (or an analogous operation) between the background orientation and the motion streak produced by object motion, it would be predicted that reduction in the availability of motion streaks would result in a veridical percept of the object's trajectory. Previous studies have well established that reducing object speed, stimulus contrast, and motion length are effective means of attenuating the salience of motion streaks (see Edwards & Crane, 2007;Li, Khuu, & Hayes, 2008). The present study adopted these stimulus manipulations and investigated whether attenuating the salience of motion streaks by reducing image speed (Experiment 1), object contrast (Experiment 2), and streak length (Experiment 3) impacts the perception of the kinetic Zollner illusion, which typifies motion-tiltinduction effects observed in kinetic geometric illusions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distortion was observed only at slow background speed, and when dots had high contrast and were of the same luminance polarity. It should be noted that in the case of Li et al [28] the motion defined shape of the object was always clearly discernable, and the speed at which moving dots affected the shape of the ellipsoid was below the critical speed for motion streaks. Indeed, dots diameter was ~6 arcmin and, based on Geisler [1], for ~6 arcmin dots, streaks start to emerge at a speed of ~2.5 deg/s.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the contracting dots induced a distortion of the illusory edges of the Kanizsa triangle along the motion direction. However, Li et al [28] showed that using a motion-defined contour, the presence of fast moving dots (speed > 2.5 deg/s) in the background did not affect the perceived shape of the motion-defined contour. In particular, the authors investigated how complex motion patterns affected the perception of shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation